2022
DOI: 10.3389/fendo.2022.1064185
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and nutrition in type 1 diabetes: Insights from the FinnDiane cohort

Abstract: Type 1 diabetes is a challenging disease, characterized by dynamic changes in the insulin need during life periods, seasons of the year, but also by everyday situations. In particular, changes in insulin need are evident before, during and after exercise and having meals. In the midst of different life demands, it can be very burdensome to achieve tight glycemic control to prevent late diabetes complications, and at the same time, to avoid hypoglycemia. Consequently, many individuals with type 1 diabetes are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Lately, overcoming the problem of hypoglycemia and maintaining normoglycemia during exercise in T1D seems quite attainable, not only due to recently available technological tools such as continuous/flash glucose monitoring systems, insulin pumps, and closed loop systems, but also specifically developed protocols regarding insulin dose adjustments and carbohydrate intake in order to prevent hypoglycemia [ 19 , 22 ]. Still, it is not clear whether one type of exercise is more suitable than another [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, overcoming the problem of hypoglycemia and maintaining normoglycemia during exercise in T1D seems quite attainable, not only due to recently available technological tools such as continuous/flash glucose monitoring systems, insulin pumps, and closed loop systems, but also specifically developed protocols regarding insulin dose adjustments and carbohydrate intake in order to prevent hypoglycemia [ 19 , 22 ]. Still, it is not clear whether one type of exercise is more suitable than another [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Better maintenance of glucose stability is associated with resistance exercise compared to aerobic exercise, although it can induce rebound hyperglycemia, probably due to increased secretion of counter-regulatory hormones [ 17 , 18 ]. Conversely, short and vigorous anaerobic exercise (for example, short sprints) or high-intensity interval training (HIIT) decreases the decline in blood glucose levels and thus has protective effects [ 19 ]. Minimization of hypoglycemia risk is attributed only to the exercise session itself; however, the current data for post-exercise hypoglycemia after anaerobic exercise do not support a clear conclusion [ 15 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of DN has shown an inverse relationship with both the intensity and frequency of exercise. A 10-year follow-up investigation involving 2180 individuals with type 1 diabetes revealed that engaging in exercise, especially at a high frequency and intensity, was associated with a decreased risk of DN advancement [15]. In longitudinal studies of alumni from the University of Pennsylvania and Harvard University, researchers followed them up to investigate the impact of physical activity on hypertension risk, classifying physical and recreational activities as light, mixed, and vigorous based on calories burned per minute (5, 7.5, and 10 kilocalories per minute).…”
Section: Protective Role Of Exercise Against Dn In Human Studiesmentioning
confidence: 99%
“…Clinical studies indicate that physical exercise can have a positive impact on the prognosis of patients with DKD. [3][4][5][6][7] This is partly due to physical exercise stimulating the secretion of a spectrum of myokines from skeletal muscles, which through endocrine and paracrine pathways, modulate the metabolism of several organs, including the adipose tissue, brain, and kidneys. [8][9][10][11] One such myokine, irisin, was identified in 2012 in the plasma of transgenic mice with muscle-specific overexpression of PGC-1α (mPGC-1α).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that moderate physical exercise can decelerate the progression of chronic kidney diseases, including DKD. Clinical studies indicate that physical exercise can have a positive impact on the prognosis of patients with DKD 3–7 . This is partly due to physical exercise stimulating the secretion of a spectrum of myokines from skeletal muscles, which through endocrine and paracrine pathways, modulate the metabolism of several organs, including the adipose tissue, brain, and kidneys 8–11 .…”
Section: Introductionmentioning
confidence: 99%